The Effect of Country of Origin on Purchase Decision at KFC Gresik, Indonesia - Veronica, Ellisa Putri; Surianto, Moh. Agung (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
This study aims to analyze the influence of Country of Origin, Price, and Servicescape on Purchasing Decisions at Kentucky Fried Chicken Wahidin Gresik. This study uses a quantitative method with a causality approach to test the cause-and-effect relationship between variables. Data were obtained from 180 respondents selected using a purposive sampling technique, with the criteria of customers who live in Gresik Regency, have purchased at Kentucky Fried Chicken Wahidin Gresik, and are aged <18 to >35 years. The results of the analysis show that Country of Origin has a significant influence on Purchasing Decisions through the attributes of production innovation, design, quality, and image of the country of origin. Price also has a significant effect on indicators of affordability, price suitability with quality, and price competition. In addition, Servicescape plays an important role in influencing customer decisions through the physical environment, spatial layout, and symbols. This study confirms that these factors significantly influence consumer purchasing behavior in the fast-food sector. The positive influence of Country of Origin, Price, and Servicescape on purchasing decisions. The practical implication is that companies need to continue to pay attention to service quality, price management, and restaurant atmosphere to improve customer experience and sales volume.